Modelling of spatio-temporal population dynamics of earthworms under wetland conditions—An integrated approach - Vorpahl, Peter; Moenickes, Sylvia; Richter, Otto (Ecological modelling, 2009)
Both the effects of earthworms on soils and the effects of soil conditions on earthworms have been studied with the help of experiments and modelling. This paper provides a model architecture allowing coupling both effects to a dynamic interaction in changing environmental conditions. We chose for a spatio-temporally explicit model and focussed on wetland conditions. Soil temperature and humidity have been modelled by means of finite volumes and were used to determine the spatial habitat suitability. The life cycles of earthworms have been modelled by Leslie matrices where soil humidity, soil temperature and population densities have been used to parametrize survival and transition probabilities. Earthworm dispersion has been described by a cellular automaton of the domain providing spatial population densities for both the life cycle submodel and the soil conditions submodel. The resulting integrated model allowed simulating the spatio-temporal population dynamics of three selected earthworm species at once in a two dimensional topological context.